Views of Global English by English and non-English Students in Indonesia - Ahmad Tauchid; Mursid Saleh; Rudi Hartono; Januarius Mujiyanto (Universitas Negeri Semarang, 2022)
Abstrak. This study focuses on English and non-English students' perspectives on their experiences with global English, along with their perceptions of the current status of English (CSE), varieties of English (VE), strategies for multilingual/multicultural communication (SMC), and English speakers' identities (ESI). There were a total of 75 participants in this survey. We used IBM SPSS Statistics 22 to perform an EFA on the collected data. Varimax rotations and principal components analysis (PCA) were used to extract data. We examined three factors: eigenvalues more than 1, factor loadings less than 0.5, and communality less than 0.5. Cronbach's alpha and composite reliability might be used to determine the sample's reliability with a value of 0.7. (CR). Cronbach's alpha values for each structure varied between 0.71 and 1.00, whereas CR values ranged between 0.79 and 0.99. Using the average variance extracted (AVE), we determined that the convergent validity varied from 0.57 to 0.97 with a 0.50 threshold. Each construct used 3 CSE items, 4 VE items, 4 SMC items, and 3 ESI items. The pooled mean and standard deviation were used to calculate descriptive statistics for the four constructs. We conducted a t-test on separate samples to see if English and non-English students' perspectives on global English varied substantially. The results suggested that neither group saw differences in their perception of the current status of English, varieties of English, strategies for multilingual/multicultural communication, and English speakers' identity. The implications of using worldwide English teaching materials and approaches are underlined.